SYNTHESIS AND COLLOID-CHEMICAL PROPERTIES OF SURFACE-ACTIVE DERIVATIVES OF BENZOIC ACID - Makhkamov R; Kurbanbaeva A; Samandarov Sh; Nurmanova M; Saidkulov F; Saidakhmedova H; Halmuminova D. (Journal Park Publishing, 2022)
The purpose of this work was synthesis of new surface-active derivatives of benzoic acid and establishing correlations between their colloid-chemical properties. The well-known methods for synthesis and determining the properties of surfactants were used in the work. The new surfactants were obtained based on the reaction of benzoic acid with sulfuric acid and different alcohols. The synthesis of new surfactants was carried out by sulfonation of benzoic acid with concentrated sulfuric acid in the presence of a catalyst and the reaction product was esterified with primary alcohols. The surface activity and foaming ability of the obtained new surfactants in aqueous solutions were studied. The obtained results showed that with an increase in the length of the aliphatic hydrocarbon chain, the surface activity of benzoic acid derivative surfactants increases. The analysis of results showed a good correlation between the foam forming ability and the surface activity of the studied surfactants. Based on the studies it was established that the stability of foams is significantly determined by the interaction of surfactant molecules in the monolayer.
Keywords: Synthesis; surfactants; colloid-chemical property